Efficient Scheduling and Collision Reduction in Hybrid Cognitive Radio Network using SBP (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Nowadays, Cognitive Radio Networks have been considered, investigated and planned in an energetic manner. But maximum works focused on separate areas like Allocation, Sensing and Sharing of Spectrum, etc.  In this paper, propose a HCRN with the subsequent characteristics of priority based scheduling based on centralized switching delay aware network and distributed broadcasting protocol to decrease collision and enhance scheduling. For developing Hybrid Cognitive Radio Networks (HCRN) lot of space is still available. The proposed HCRN is simulated and network quality of service is estimated in terms of packet delivery ratio, control overhead, throughput and broadcast delay.